Exploring Buddhism. - Humphreys, Christmas (Routledge revivals., 2012)
The Buddhist field of knowledge is now so vast that few can master all of it, and the study and application of its principles must be a matter of choice. One may choose the magnificent moral philosophy of Theravada, the oldest school, or the Zen training of Japan; or special themes such as the doctrine of No-self, the Mahayana emphasis on compassion or the universal law of Karma and Rebirth. But the intense self-discipline needed for true spiritual experience calls for specialization of subject and technique. In this reissue, first published in 1974, Christmas Humphreys takes us on a personal.